2017
DOI: 10.1007/s00775-017-1450-7
|View full text |Cite
|
Sign up to set email alerts
|

EGFR-targeting peptide-coupled platinum(IV) complexes

Abstract: The high mortality rate of lung cancer patients and the frequent occurrence of side effects during cancer therapy demonstrate the need for more selective and targeted drugs. An important and well-established target for lung cancer treatment is the occasionally mutated epidermal growth factor receptor (EGFR). As platinum(II) drugs are still the most important therapeutics against lung cancer, we synthesized in this study the first platinum(IV) complexes coupled to the EGFR-targeting peptide LARLLT (and the shuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…For conjugation a Cys‐miniPEG linker was attached to the LARLLT peptide sequence. We synthesized the transcyclization product 5a using 24 h incubation of the peptide and the maleimide‐bearing platinum complex in PB pH 7.4, [8] resulting in ∼95 % conversion to 5a . For the thiosuccinimide reference complex 5b we protected the terminal Cys via acetylation.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…For conjugation a Cys‐miniPEG linker was attached to the LARLLT peptide sequence. We synthesized the transcyclization product 5a using 24 h incubation of the peptide and the maleimide‐bearing platinum complex in PB pH 7.4, [8] resulting in ∼95 % conversion to 5a . For the thiosuccinimide reference complex 5b we protected the terminal Cys via acetylation.…”
Section: Figurementioning
confidence: 99%
“…In ar ecent publication, we synthesized ad rug-peptide conjugatev ia reactiono famaleimide moiety and an N-terminal cysteinef or coupling. [8] High-performance liquid chromatography/mass spectrometry( HPLC-MS)m easurements revealed that the product peak converted within severalh ours into a new peak with the same exact mass. This reaction was supposed to be aM ichael-transcyclization already known from similars ystems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following a different approach, the incorporation of a maleimide fragment enabled specific interactions with proteins (e.g., addition to thiol residues) for compounds showing a promising anticancer activity in vivo [261,268,369]. The conjugation with suitable targeting groups, to enhance the pharmacological performance, can be achieved via modification of either the axial carboxylato co-ligand [367,370] or the carbamato ligand itself [272,371,372]. Remarkably, all of these Pt(IV) complexes are stable for several hours or even days in physiological aqueous solutions [260,261,263,272].…”
Section: Other Applicationsmentioning
confidence: 99%
“…20,21 This prodrug strategy has been widely used for the construction of multifunctional Pt complexes as illustrated in many studies. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] BRCA and RAD51 play essential roles in HR, and BRCA-procient tumors are usually refractory to CDDP due to effective HR. Recently, we designed two Pt IV -artesunate prodrugs, which inhibited HR via downregulating RAD51 and exhibited higher cytotoxicity against BRCA-procient cancer cells than CDDP.…”
Section: Introductionmentioning
confidence: 99%